(untitled) (Mustansiria Dental Journal, 2018)
Background: The fracture of instruments within root canal during endodontic treatment is a common incidence, fracture of fatigue through flexure occurs because of metal fatigue, NaOCl used for irrigation may have an effect on corrosion that decrease fracture resistance. This study aimed to assess the effect of NaOCl temperature on the cyclic fatigue of different type of Endodontic NiTi Rotary Instruments and compare among them. Materials and method: three types of rotary instruments with tip size 0.25: ProTaPer F2 (Densply,Malifier) Revo-S SU ( 0.06 taper, MicroMega) and RaCe system (0.06 taper, FKG,Dentaire), Thirty file of each instrument type were used within canal with 60° angle of curvature , undiluted NaOCl (5.25% ) were used. Ten file without immersion in NaOCl, ten were immersed at room temperature (21°C) for 5 minute and ten with immersion in NaOCl at 60°C for the same time. Nine group were formed for all instruments (total number=90). The testing canal customized within stainless steel block covered with glass face, the time to fracture recorded and the mean of cycles to fracture (MCF) detected for each instrument .Data were analyzed statistically by ANOVA, LSD and Independent T-test at 5% significant level. Result: there was a highly significant difference in mean of cycles to fracture for each rotary instrument when temperature of NaOCl increased that the Number of cycles to fracture decreased as the temperature increased. RaCe revealed the best fracture resistance followed by ProTaper then Revo-s that showed the less resistance. Conclusion: the rotary instruments more prone to fracture when temperature of NaOCl increased, as well as the rotary instruments differ from each other according to manufacturing process, taper, cross section and other factors.